RELEVANCE OF FINANCIAL RATIOS TO DETERMINE THE DIVIDEND YIELD IN MANUFACTURING COMPANY LISTED ON INDONESIA STOCK EXCHANGE 2005 - 2009 - Eric Purniawan; Mukhtaruddin Mukhtaruddin (AKUNTABILITAS, 2012)
This study aims to determine the effect of financial ratios information to predict theDividend Yield. The financial ratios are projected into five independent variables, namelyNet Profit Margin (NPM), Return On Equity (ROE), Return On Asset (ROA), Return Oninvestment (ROI), and Debt to Equity (DER), and one dependent variable, namelyDividend Yield (DY).The population in this research are all of manufacturing companies that listed onIndonesia Stock Exchange in 2009 as many as 139 companies. By using the purposivejudgement sampling, it was determined there are 25 companies that are used as researchsamples. All data used in this research are secondary data that obtained from theIndonesia Stock Exchange's official website. The data analysis tool in this research is alinier regression because the independent and dependent variable in this research is inpercentage ratios variable. The data analysis techniques in this research includedescriptive statistical tests, classical test assumption and the linier regression test bothsimultaneously or separately.From the analysis of hypothesis testing simultaneously, it can be concluded that allindependent variables in this research have significant effect against Dividend yield inmanufacturing companies that listed on Indonesia Stock Exchange (2005 – 2009) with asignificant level sig= 0,012. From the analysis of hypothesis testing separately, it can beconcluded that only two variables that have a significant effect against Dividend Yield,those are Net Profit Margin (NPM) and Return On equity (NPM) with a significant levelsig= 0,029 and sig=0,038, so those variables are reliable in predicting the level ofinvestment gains (Dividend Yield).